The fifth development plan - Ahmad Naini (Intereconomics, 1975)
The four development plans, under which Iran has gone forward on a continuous course of industrialization since 1949 were followed by a Fifth Development Plan, which came into force in March 1973. This fifth plan had however to be revised recently: the expenditure on investments is to be doubled compared with the original plan.
Keywords: 330; Iran